Socio-Political, Military Lexicon in the Work “Shajarayi Tarokima” (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This articles analyzes socio-political and military lexemes in the in the work “Shajarayi tarokima” created by the Khiva Khan Abulgoziy Bahodirkhan in the 17 th-18th centuries using statistical and comparative –historical methods. The etymology of some terms is explained using dictionaries, scientific literature and sources.